Multiple directorships, board characteristics and firm performance in Malaysia - Abdul Latif, Rohaida; Kamardin, Hasnah; Taufil Mohd, Kamarun Nisham; Che Adam, Noriah (Scientific & Academic Publishing, 2013)
The objective of the study is two-fold.First, the study examines the extent of multiple directorship practices of Malaysian public listed companies.Secondly, the study assesses the relationship of several board characteristics with firm performance.Using a sample of 132 companies in 2008, the result shows that almost 90% of directors of Malaysian public listed firms have between 1 to 3 directorships. The multiple directorships affect firms’ market performance positively but not significantly.Ex government officials and founders have positive and significant influence on performance.Family ownership is significant and has U-shaped relationship with performance. The findings to some extent have policy implication to corporate governance practices